2015
DOI: 10.1039/c5tb02080h
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in situ endothelialization of a small diameter vascular graft with catalytic nitric oxide generation and promoted endothelial cell adhesion

Abstract: Rapidin situendothelialization of a small diameter vascular graft with catalytic nitric oxide generation and promoted endothelial cell adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…20,108113 Many researchers have later unveiled NO’s various physiological functions in the human body, including preventing platelet activation and adhesion, inhibiting bacterial proliferation and biofilm formation, enhancing endothelization, signaling in the immune system’s response, and promoting angiogenesis and the wound healing process. 112,114117 …”
Section: Nitric Oxide (No) To the Rescuementioning
confidence: 99%
See 1 more Smart Citation
“…20,108113 Many researchers have later unveiled NO’s various physiological functions in the human body, including preventing platelet activation and adhesion, inhibiting bacterial proliferation and biofilm formation, enhancing endothelization, signaling in the immune system’s response, and promoting angiogenesis and the wound healing process. 112,114117 …”
Section: Nitric Oxide (No) To the Rescuementioning
confidence: 99%
“…The NO-releasing grafts were found to be substantially less thrombogenic than the controls, suggesting considerable promise for this approach to improve the performance of vascular graft after implantation. 239 The West 115 and Wang 114 groups both reported that NO releasing/generating grafts encourage endothelialization/endothelial cell proliferation, which can alleviate the complications of thrombosis and intimal hyperplasia (IH) that cause the failure of small diameter vascular grafts without the use of systemic anticoagulants.…”
Section: Applications Of No Releasing/generating Polymers For Preparimentioning
confidence: 99%
“…in the untreated. (100) Other authors have attached cell-adhesive peptides (101105) or added cell-friendly biochemicals (102,103,105107) to entice engraftment.…”
Section: Designs and Progressmentioning
confidence: 99%
“…Besides peptides such as RGD, which induce cell adhesion in general, peptide sequences have been discovered for which specific cell types have an increased affinity over other cell types, due to increased expression of the binding motif on these cells . The REDV peptide, for which endothelial cell‐specificity has been reported, attributed to binding to integrin α4β1, has been extensively applied to enhance endothelialization of biomaterials . In another approach, a peptide derived from stromal cell derived factor‐1α (SDF1α), a chemoattractant of lymphocytes, monocytes, and progenitors cells, has been applied for improved in situ cellularization…”
Section: Introductionmentioning
confidence: 99%